Endothelial Cell Protein S Synthesis Is Upregulated by the Complex of IL-6 and Soluble IL-6 Receptor - Hooper, W Craig; Phillips, Donald J; Evatt, Bruce L (Thrombosis and Haemostasis, 1997)
We have recently demonstrated that the proinflammatory cytokine, interleukin-6 (IL-6), could upregulate the production of protein S in the human hepatoma cell line, HepG-2, but not in endothelial cells. In this study, we have demonstrated that the combination of exogenous IL-6 and soluble IL-6 receptor (sIL-6R) could significantly upregulate protein S production in both primary human umbilical vein endothelial cells (HUVEC) and in the immortalized human microvascular endothelial cell line, HMEC-1. The IL-6/sIL-6R complex was also able to rapidly induce tyrosine phosphorylation of the IL-6 transducer, gpl30. Neutralizing antibodies directed against either IL-6 or gpl30 blocked protein S upregulation by the IL-6/sIL-6R complex. It was also observed that exogenous sIL-6R could also upregulate protein S by forming a complex with IL-6 constitutively produced by the endothelial cell. Two other cytokines which also utilize the gpl30 receptor, oncostatin M (OSM) and leukemia inhibitory factor (LIF), were also able to upregulate endothelial cell protein S. This study demonstrates a mechanism that allows endothelial cells to respond to IL-6 and also illustrates the potential importance of circulating soluble receptors in the regulation of the anticoagulation pathway.